2014
DOI: 10.1016/j.nuclphysb.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Level two string functions and Rogers Ramanujan type identities

Abstract: The level two string functions are calculated exactly for all simply laced Lie algebras, using a ladder coset construction. These are the characters of cosets of the type G/U (1) r , where G is the algebra at level two and r is its rank. This coset is a theory of generalized parafermions. A conjectured Rogers Ramanujan type identity is described for these characters. Using the exact string functions, we verify the Rogers Ramanujan type expressions, that are the main focus of this work.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Also, for the level two simply laced algebras a GRR expression was described in refs. [7,8], and our formula here specialises precisely to these level two results. Thus our formula, eq.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Also, for the level two simply laced algebras a GRR expression was described in refs. [7,8], and our formula here specialises precisely to these level two results. Thus our formula, eq.…”
mentioning
confidence: 81%
“…Several examples of characters in CFT were studied, and were shown to be expressible as Rogers Ramanujan type sums [2,3,4,5,6,7,8]. The origin of these identities is somewhat perplexing, though, they were shown to be connected with local state probabilities in solvable lattice models [9,10,11], and with thermodynamic Bethe ansatz equations (see, e.g., [6] and refs.…”
mentioning
confidence: 99%
“…Interestingly, it was shown that the A type parefermions theories of level two and any rank can be realised by a product theory of minimal models with particular combinations of the representing fields taken to insure modular invariance is preserved. This was followed by [7] where this program was generalized to all simply laced affine Lie algebras and the characters of ADE generalized parafermions at level two and any rank were also found. More specifically, the authors of [2] considered the coset A(k, r) = H × SU (r) k × SU (k) r × SU (k) n SU (k) r+n (1.3) corresponding to the construction described above for the k M 5-branes on R 4 /Z N instanton partition function where n is given in terms of the Nekrasov parameters 1,2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind the authors of [2] conjectured and numerically verified GRR identities for the A type generalized parafermion characters. Furthermore, an ADE generalization for level two parafermions soon followed and also verified numerically in [7]. Finally although, only ADE level two generalized parafermions characters were given exact analytical expressions the corresponding GRR identities led to a conjecture for the characters of generalized parafermions associated with any Lie algebras at any level and rank level [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation